2017
DOI: 10.1093/ehjci/jex257
|View full text |Cite
|
Sign up to set email alerts
|

Understanding decision-making in cardiac imaging: determinants of appropriate use

Abstract: Factors that influenced the ordering of echocardiograms by clinicians at a tertiary care hospital did not appear to be amenable to control with AUC. Alternative approaches may be more effective than the AUC in addressing the overuse of echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(82 citation statements)
references
References 31 publications
4
78
0
Order By: Relevance
“…"I'm often a bit defensive...I guess that's partly that legal thing" [38] "I think the whole medical-legal thing also makes people more inclined to CT [computed tomography] someone even if they have a pretty low suspicion just 'cause no one wants to be sued" [39] "I think litigation is a problem; you miss one neck... fracture or bleed in the brain you are going to court" [47] Factor Articles Illustrative quotes Clinician knowledge and understanding 25 articles [2,3,5,15,29,32,33,35,37-39,42−44,47,52,53,59−66] "How much work [laboratory testing] is, how much it costs, how much normal results can uctuate, things like that, I think we know very little about that" [3] "Nothing can really go wrong [with overutilization]" [3] "You understand the natural course of disease and the point in time at which you have to make a decision to do something different" [29] "When I'm admitting a patient or doing clinical work, it's kind of affected my thought process to where I think a little bit more about 'do I really need to get this test? ', 'will it really change management?…”
Section: Results Of Narrative Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…"I'm often a bit defensive...I guess that's partly that legal thing" [38] "I think the whole medical-legal thing also makes people more inclined to CT [computed tomography] someone even if they have a pretty low suspicion just 'cause no one wants to be sued" [39] "I think litigation is a problem; you miss one neck... fracture or bleed in the brain you are going to court" [47] Factor Articles Illustrative quotes Clinician knowledge and understanding 25 articles [2,3,5,15,29,32,33,35,37-39,42−44,47,52,53,59−66] "How much work [laboratory testing] is, how much it costs, how much normal results can uctuate, things like that, I think we know very little about that" [3] "Nothing can really go wrong [with overutilization]" [3] "You understand the natural course of disease and the point in time at which you have to make a decision to do something different" [29] "When I'm admitting a patient or doing clinical work, it's kind of affected my thought process to where I think a little bit more about 'do I really need to get this test? ', 'will it really change management?…”
Section: Results Of Narrative Reviewmentioning
confidence: 99%
“…Need to explain the limitation of check-ups" [ "Lab testing is often only done for the doctor's peace of mind." [3] "I am worried if they don't have a full assessment and I miss something that it is going on with their heart that is not apparent because ECGs [electrocardiograms] and clinical examinations are not very precise" [29] "You're sitting there with someone who has a sudden-onset splitting headache, but otherwise you see nothing alarming… A CT scan for an acute headache. Even if the pre-test chance is 0.01.…”
Section: Results Of Narrative Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In a qualitative study addressing the determinants of appropriate use of echocardiography, Fonseca and colleagues22 found that physician factors including training, experience, handling uncertainty and perception of peer and patient expectations influenced echocardiogram use. Similarly, Hisham and colleagues23 found that despite having positive attitudes about evidence and CPGs, doctors’ practice was often not evidence-based due to barriers including heavy workload and workplace culture.…”
Section: Discussionmentioning
confidence: 99%